New Trends in Medical and Service Robots Assistive, Surgical and Educational Robotics - Bleuler, Hannes; Bouri, Mohamed; Mondada, Francesco; Pisla, Doina; Rodić, Aleksandar; Helmer, Patrick; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Medical and Service Robotics integrate the most recent achievements in mechanics, mechatronics, computer science, haptic and teleoperation devices together with adaptive control algorithms. The book  includes topics such as surgery robotics, assist devices, rehabilitation technology, surgical instrumentation and Brain-Machine Interface (BMI) as examples for medical robotics. Autonomous cleaning, tending, logistics, surveying and rescue robots, and elderly and healthcare robots are typical examples of topics from service robotics. This is the Proceedings of the Third International Workshop on Medical and Service Robots, held in Lausanne, Switzerland in 2014. It presents an overview of current research directions and fields of interest. It is divided into three sections, namely 1) assistive and rehabilitation devices; 2) surgical robotics; and 3) educational and service robotics. Most contributions are strongly anchored on collaborations between technical and medical actors, engineers, surgeons and clinicians. Biomedical robotics and the rapidly growing service automation fields have clearly overtaken the "classical" industrial robotics and automatic control centered activity familiar to the older generation of roboticists.
Preface -- Part I Assistive and Rehabilitation Devices -- Study and choice of actuation of a walking assist device, by Y. Aoustin, C. Chevallereau and V. Arakalian -- Hybrid Adaptive Low Cost Support Device For FES Stroke Rehabilitation, by G. Cannella, D. S. Laila and C. T. Freeman -- Motion Control Algorithm of Walking Assist Machine Using Crutches to Achieve Variable Gait Style and Step Length, by D. Matsuura, R. Inose and Y. Takeda -- On developing lightweight robot-arm of anthropomorphic characteristics, by A. Rodić, B. Miloradović, S. Popić and D: Urukalo -- Towards a natural interface for the control of a whole arm prosthesis, by G. Gini, P. Belluco and F. Mutti -- Design & Simulation of an Orthotic Device for Patients with Osteoarthritis, by D. Tarnita, M. Catana, N. Dumitru and D.N. Tarnita -- Kinematic and Dynamic Study Contributions on Human Jaw System, by N. Dumitru, C. Copilusi and M. Ciortan -- A Robotic Platform for Lower Limb Optical Motion Tracking in Open Space, by A. Ortlieb, J. Olivier, M. Bouri and H. Bleuler -- Part II Surgical Robotics -- Virtual Planning of Needle Guidance for a Parallel Robot used in Brachytherapy, by B. Gherman, T. Girbacia, D. Cocorean, C.Vaida, S. Butnariu, N. Plitea, D. Talaba and D Pisla -- Sensory subtraction via cutaneous feedback in robot-assisted surgery, by L. Meli, C. Pacchierotti and D. Prattichizzo -- Active Bending Electric Endoscope Using Shape Memory Alloy Wires, by T. Kobayashi, T. Matsunaga and Y. Haga -- Kinematic Analysis of Instruments for Minimally Invasive Robotic Surgery: Generalization of the Reference Task, by B. Deutschmann, R. Konietschke, C. Ott -- Third Arm Manipulation for Surgical Applica-tions: An Experimental Study, by E. Abdi, M. Bouri, S. Himidan, E. Burdet and H. Bleuler -- Robotic Surgical Approach in Limited Access Anatomical Areas, by N. Crisan, Iulia Pop and I. Coman -- Part III Educational and Service Robotics -- Ranger, an Example of Integration of Robotics into the Home Ecosystem, by F. Mondada, J. Fink, S. Lemaignan, D. Mansolino, Florian Wille and Karmen Franinovic -- Design and control of humanoid robot MARKO: an assistant in therapy for children, by B. Borovac, M. Raković, S. Savić, and M. Nikolić -- Give Children Toys Robots to Educate and/or NeuroReeducate: the exemple of PEKOPPA, by I. Giannopulu and T. Watanabe -- Automatic segmentation of therapeutic exercises motion data based on a predictive event approach, by S. Spasojevic and R. Ventura -- Arm motions of a humanoid inspired by human motion, by M. Tomic, C. Vassallo, C. Chevallereau, A. Rodic and V. Potkonjak -- Development of a Virtual Testing Platform within an Instructor Operation Station, by A. Pisla, D. Cocorean, C. Vaida and D. Pisla.
Keywords: Control engineering; Robotics; Automation; Biomedical engineering; User interfaces (Computer systems).; Human-computer interaction; Endoscopic surgery; Control, Robotics, Automation; Biomedical Engineering and Bioengineering; User Interfaces and Human Computer Interaction; Minimally Invasive Surgery